2017
DOI: 10.1007/s40596-017-0766-5
|View full text |Cite
|
Sign up to set email alerts
|

Personality Traits Are Associated with Academic Achievement in Medical School: A Nationally Representative Study

Abstract: This study suggests the importance of personality traits, particularly conscientiousness, in predicting success during the clinical years of medical school. Medical educators should consider a nuanced examination of personality traits and other non-cognitive factors, particularly for psychiatry.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
25
0
4

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(36 citation statements)
references
References 29 publications
2
25
0
4
Order By: Relevance
“…In contrast, 'neuroticism' which is related to emotional instability is negatively associated with academic achievement (Chamorro-Premuzic & Furnham 2003). Students high in 'neuroticism' are less likely to do well in most specialties (Sobowale et al 2018). These findings may confirm the significance of personality traits generally even though the students' learning styles and methods still need further investigation.…”
Section: Introductionmentioning
confidence: 94%
“…In contrast, 'neuroticism' which is related to emotional instability is negatively associated with academic achievement (Chamorro-Premuzic & Furnham 2003). Students high in 'neuroticism' are less likely to do well in most specialties (Sobowale et al 2018). These findings may confirm the significance of personality traits generally even though the students' learning styles and methods still need further investigation.…”
Section: Introductionmentioning
confidence: 94%
“…When examining the relationship between academic success and general personality characteristics, the most frequently assessed traits are the Big Five personality traits. Conscientiousness (e.g., Barrick & Mount, 1991;Noftle & Robins, 2007;Richardson & Abraham, 2009;Saklofske, Austin, Mastoras, Beaton, & Osborne, 2012), agreeableness (e.g., Saklofske et al, 2012;Shiner, Masten, & Roberts, 2003), and openness (e.g., Bauer & Liang, 2003;Moses et al, 2011;Noftle & Robins, 2007) are consistently indicated as significant positive predictors of GPA or other indicators of academic success, with conscientiousness being the strongest overall predictor (Poropat, 2009;Richardson, Abraham, & Bond, 2012;Rimfeld, Kovas, Dale, & Plomin, 2016;Sobowale, Ham, Curlin, & Yoon, 2018;Stajkovic, Bandura, Locke, Lee, & Sergent, 2018;Vedel, 2014). The research examining the relationship between neuroticism and GPA is mixed, with some studies finding significant negative relationships (e.g., Chamorro-Premuzic, 2006;Chamorro-Premuzic & Furnham, 2003) and others finding significant positive relationships (e.g., Musgrave-Marquart, Bromley, & Dalley, 1997;Noftle & Robins, 2007;Steele-Johnson & Leas, 2013).…”
Section: Personalitymentioning
confidence: 99%
“…En cuanto a este interés y motivación necesarios para el ejercicio de la investigación científica, existe literatura sobre diversas iniciativas de investigación que se centran en descubrir los factores relacionados al éxito académico en el contexto universitario (Borracci et al, 2014;Mills, Heyworth, Rosenwax, Carr & Rosenberg, 2009). Estos estudios claramente evidencian que la personalidad humana está fuertemente vinculada a procesos internos de los individuos y sus motivaciones en el campo académico, que, en consecuencia, generan un adecuado rendimiento académico y un importante grado de motivación de logro ante tareas y exigencias como las que demandan aquellas que implican rigor científico (Al-Naggar et al, 2015;Chamorro-Premuzic & Furnham, 2008;Eyong, David & Umoh, 2014;Hakimi, Hejazi & Lavasani, 2011;Mamani & Quinteros, 2014;Sobowale, Ham, Curlin & Yoon, 2017;Tijdink et al, 2016;Vedel & Poropat, 2017).…”
Section: Traço De Consciência E Atitude Em Relação à Tese Em Estudantunclassified
“…Así también, respecto a iniciativas que vinculan netamente los rasgos de personalidad con la actitud hacia la tesis en universitarios, se resalta el trabajo realizado por Mamani y Quinteros (2014), quienes también concluyeron que cuanto mayor predominancia tiene el rasgo conciencia en el perfil de personalidad de los estudiantes, mayores actitudes favorables hacia la tesis son reveladas. Por otra parte, en el ámbito internacional, donde aparecen la mayor cantidad de estudios que avalan que la personalidad, es evidente que este rasgo ha demostrado ser un predictor para determinar un buen desempeño y éxito académico (Al-Naggar et al, 2015;Chamorro-Premuzic & Furnham, 2008;Eyong, David & Umoh, 2014;Hakimi, Hejazi & Lavasani, 2011;Sobowale, Ham, Curlin & Yoon, 2017;Tijdink et al, 2016;Vedel & Poropat, 2017), resaltando algunos como el realizado por Hong y Li (2011), quienes concluyeron que el rasgo conciencia es un predictor significativo de actitudes favorables hacia la ciencia en estudiantes de educación secundaria. Así también, el realizado por Malykh (2017), el cual concluye que el único rasgo de personalidad que tiene la capacidad de explicar las diferencias individuales respecto al logro académico en una población de estudiantes de secundaria, fue el denominado rasgo o factor conciencia.…”
Section: Traço De Consciência E Atitude Em Relação à Tese Em Estudantunclassified